2013
DOI: 10.1186/1999-3110-54-23
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth and carbon utilization of the green-leaved orchid Dendrobium officinale are promoted by mycorrhizal associations

Abstract: BackgroundMycorrhizal associations play a key role in the life cycle and evolutionary history of orchids. All orchids grow from extremely small seeds that are lacking in reserves, and germination and growth into an underground heterotrophic, achlorophyllous stage depend upon symbiotic fungi to provide nutrient. However, the nutritional physiology between this symbiosis and green-leaved orchids is still unclear. To understand further how these associations affect growth and carbon utilization of green orchids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Generally, sucrose synthesis is considered to be catalyzed by SPS (in conjunction with sucrose phosphatase, which maintains the cytosolic concentration by rapidly removing sucrose-6-phosphate), whereas sucrose breakdown is largely catalyzed by SuSy and invertase (Huber and Huber, 1996) ( Figure 5A). Wang et al (2013) analyzed the correlation between soluble polysaccharide and sucrose metabolic enzymes in D. officinale and found that the level of polysaccharides is directly affected by the concentration of the reduced sugar in the cell, and the level of reduced sugar and soluble sugar is related to the activity of sucrose invertase and SPS (Wang, 2009) ( Figure 5A). We identified 10 SPS genes and 15 SuSy genes in D. officinale, which have undergone marked expansion through tandem duplication (only a few genes in other plant genomes, Figure 5C).…”
Section: Molecular Plantmentioning
confidence: 99%
“…Generally, sucrose synthesis is considered to be catalyzed by SPS (in conjunction with sucrose phosphatase, which maintains the cytosolic concentration by rapidly removing sucrose-6-phosphate), whereas sucrose breakdown is largely catalyzed by SuSy and invertase (Huber and Huber, 1996) ( Figure 5A). Wang et al (2013) analyzed the correlation between soluble polysaccharide and sucrose metabolic enzymes in D. officinale and found that the level of polysaccharides is directly affected by the concentration of the reduced sugar in the cell, and the level of reduced sugar and soluble sugar is related to the activity of sucrose invertase and SPS (Wang, 2009) ( Figure 5A). We identified 10 SPS genes and 15 SuSy genes in D. officinale, which have undergone marked expansion through tandem duplication (only a few genes in other plant genomes, Figure 5C).…”
Section: Molecular Plantmentioning
confidence: 99%
“…Therefore, the use of mycorrhizal fungi from germination aims to improve the growth and development of the seedlings, even in cases in which in vitro germination does not require the presence of the symbiotic process to occur, in order to ensure greater future gains during the acclimatization phase (Wang et al 211, Dan et al 2012). The use of MS (Murashige & Skoog 1962), a traditional medium to symbiotic orchids seedling development, was related by Wang et al (2013) in the symbiotic cultivation of Dendrobium officinale Kimura et Migo and, according to Bocayuva et al 2014, the addition of macro and micronutrients to the OMA medium provides the production of more developed Hadrolaelia jongheana (Rchb.f.) Chiron & V. P. Castro plants, without inhibiting the mycorrhizal growth in ten months, resulting in an efficient and faster protocol to conduct the later stages of acclimatization and in situ reintroduction for species conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from this study will be alternative way for conservation and propagation of this endangered orchid in Thailand. (Rasmussen, 1995;Bidartondo et al, 2004;Smith and Read, 2010) ต้ นกล้ าของกล้ วยไม้ บางชนิ ดสามารถส่ งสารอาหารที ่ ได้ จากกระบวนการสั งเคราะห์ ด้ วยแสงให้ แก่ รา ไมคอร์ ไรซาได้ (Cameron, Leake and Read, 2006;Wang et al, 2013) (Burgeff, 1936cited in Huynh et al, 2004) ส่ วนในกล้ วยไม้ S. plicata พี โลตอนจะเริ ่ มถู กย่ อยในวั นที ่ 10 หลั งจากการเริ ่ มสร้ าง พี โลตอน (Senthilkumar and Krishnamurthy, 1998) ในกล้ วยไม้ บางชนิ ด การเข้ าติ ดเชื ้ อของรา ในโปรโตคอร์ มกล้ วยไม้ เกิ ดขึ ้ นโดยใช้ เวลา 14 ชั ่ วโมง สร้ างพี โลตอนในเวลา 29 ชั ่ วโมง และย่ อยสลาย ภายในเวลา 40 ชั ่ วโมง (Hadley and Williamson, 1971) (Peterson and Currah, 1990) Peterson and Currah (1990) ศึ กษาพบชั ้ นเมื อกเซลลู โลสในโปรโตคอร์ มกล้ วยไม้ ใน การศึ กษาต่ อมาพบว่ า ชั ้ นดั งกล่ าวไม่ ใช่ เซลลู โลสแต่ เป็ นแคลโลส (callose) (Senthilkumar and Krishnamurthy, 1998) ซึ ่ งเป็ นพอลี แซกคาไรด์ ของน้ ้ าตาลกลู โคส ที ่ มี คุ ณสมบั ติ ไม่ ยอมให้ สารซึ มผ่ าน เป็ นสารที ่ พื ชหลั ่ งออกมาเพื ่ อป้ องกั นไม่ ให้ เซลล์ ถู กท้ าลายเมื ่ อเกิ ดบาดแผล พบสารแคลโลสสะสมมาก บริ เวณที ่ มี การเสื ่ อมสลายของพี โลตอนของรา Rhizoctonia cerealis ในกล้ วยไม้ P. hyperborean (Richardson, Peterson and Currah, 1992) (Senthilkumar and Krishnamurthy, 1998 (Peterson and Currah, 1990 (Otero, Ackerman and Bayman, 2002;Bougoure et al, 2005;Bonnardeaux et al, 2007 (Ma, Tan and Wong, 2003 (Peterson and Currah, 1990) (Williamson and Hadley, 1970 (Hadley, 1975;Peterson and Currah, 1990) พบการสร้ างชั ้ น ของเหลว (Interfacial matrix) ระหว่ างไซโทพลาสซึ มของเซลล์ กล้ วยไม้ กั บเส้ นใยราภายในเซลล์ กล้ วยไม้ พบเอนไซม์ ATPases ทั ้ งในเซลล์ พื ชและเส้ นใยรา โดยเอนไซม์ อยู ่ ในภาวะพร้ อมท้ างาน ขณะที ่ เกิ ดการย่ อยสลายของเส้ นใย และพบแอกทิ วิ ที ของเอนไซม์ ฟอสฟาเทส (phosphatase activity) ในชั ้ นของเหลวและเยื ่ อหุ ้ มเซลล์ ของพื ช แสดงให้ เห็ นว่ าเซลล์ พื ชเป็ นแหล่ งสร้ างของเหลว ดั งกล่ าว (Serrigny and Dexheimer, 1985) โดยระยะเวลาในการเข้ าติ ดเชื ้ อ การสร้ างและย่ อย สลายพี โลตอนแตกต่ างกั นในแต่ ละชนิ ดของกล้ วยไม้ จากการศึ กษาของ…”
unclassified